(untitled) (Research, Society and Development, 2020)
The objective of the text is to analyze the teaching professionalization process to work in distance learning courses in Natural Sciences and Mathematics at the Federal Institutes of Education, Science and Technology (IFs) in Brazil. The phenomenological methodology materialized by (a) locating, among all the IFs in Brazil, the courses object of the research; (b) analyzing their institutional arrangements and, (c) analyzing, collating and reflecting, through ideographic and nomothetic analysis, the phenomenon in question. It is concluded that teacher professionalization is the result of initial and continued conscious training and guided by trajectories that reflect on the training process, the work space and its relationship with the desired world.